The Library of Leufstabruk - Sjökvist, Peter (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
The eighteenth‑century library at the magnificent iron making estate of Leufstabruk one hour north of Uppsala (Sweden) is located in a small exquisite pavilion next to the manor house. There the absolute majority of the books are kept until this day in their original places, arranged according a system of the time. Having been an entailed estate within the noble family with Dutch origins De Geer from 1730 until 1986, the collections of today most of all mirror the interests of its member Charles (1720–1778), as well as to a minor degree his son Charles (1746–1805), his daughter Hedvig Ulrika (1752–1813) and some more. The present article wants to give an updated image of this library, based on previous research as well as a recently finished infrastructure project, whereby knowledge of and access to its collections, which are awaiting to be explored further, have been strongly increased.